Analysis of Factors Determining Company Value with Company Size as a Moderation Variable in Companies Listed on the Indonesia Stock Exchange (IDX) for the 2021 – 2024 Period - Rina Sulistiyowati; Peng Wi; Trida Trida (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This research has the objective of whether partial profitability, leverage, liquidity, sales growth, company size affect the value of the company. and whether profitability, leverage, liquidity, sales growth, the size of the company by being moderated by the size of the company has an effect on the value of the company. This type of research is qualitative descriptive with a sample in the study of 22 companies that meet the criteria while the data analysis used SmartPLS. Based on the results of the research, profitability and leverage have a positive and significant effect on the company's value. Liquidity, sales growth, and company size do not have a significant effect on the company's value. Meanwhile, the results of moderation of company size are proven to be significant in the relationship between leverage and liquidity to company value and company size is not significant in the relationship between profitability and sales growth to the value of the company. This shows that the influence of these two variables is not influenced by the size of the company.